2009
DOI: 10.1016/j.ijsolstr.2009.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Variation-based cracked laminate analysis revisited and fundamentally extended

Abstract: a b s t r a c tThe analyses of cracked laminates based on a variational principle and related approaches are appraised in this paper. The limitations of the existing methodology on the analyses of more general laminate configurations have been identified. It has been revealed that the limiting factor is the lack of boundary conditions for uncracked laminae. Natural boundary conditions have then been derived from the variational principle to meet the need. Such boundary conditions are mathematically sound but c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Vinogradov and Hashin (2010) extended the analysis to angle-ply laminates of type [θ m /φ n ] s containing intralaminar cracks in the middle laminae and found that prediction for the Young's modulus of cracked GFRP angle-ply [0/45] s is in good agreement with experimental results of Katerelos et al (2006). In the recent years the variational approach has gained significant attention (e.g., Li and Hafeez 2009;Katerelos et al 2015).…”
Section: Introductionmentioning
confidence: 80%
“…Vinogradov and Hashin (2010) extended the analysis to angle-ply laminates of type [θ m /φ n ] s containing intralaminar cracks in the middle laminae and found that prediction for the Young's modulus of cracked GFRP angle-ply [0/45] s is in good agreement with experimental results of Katerelos et al (2006). In the recent years the variational approach has gained significant attention (e.g., Li and Hafeez 2009;Katerelos et al 2015).…”
Section: Introductionmentioning
confidence: 80%
“…Similar to what was demonstrated by Li and Hafeez, 9 the physical boundary conditions are generally insufficient to determine the unknown constants and the so-called "natural boundary conditions" are required, which in the variational calculus result from integration by parts of the perturbed functional. For the quadratic Lagrangian (29), these natural boundary conditions are given by dF…”
Section: Natural Bcmentioning
confidence: 68%
“…In all studies that adopted the generalized variational approach of Li and Hafeez, 9 two inherent steps are present: (1) derivation of natural boundary conditions, whose solution together with physical boundary conditions leads to the stress field in a cracked laminate, and (2) application of specific loading and integration of the resultant stress energy density to evaluate the complementary energy and corresponding compliances of the laminate. Analysis in the present paper addresses the problem of intralaminar cracks in an general laminate, when cracks are in plies with parallel fiber orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The one single fundamental assumption is that the inplane transverse and shear stresses are linear through-thickness of each ply. Akin to the variational models developed for ply cracking [15][16][17][18][19][20][21][22][23], the total stresses/displacements in a composite with free edges are partitioned to unperturbed (without free edge) and perturbation stresses/displacements. Therefore, it is possible to consider the effects of applied thermo-mechanical loads in the unperturbed state leading to a system of homogeneous differential equations that can be solved using standard methods.…”
Section: Introductionmentioning
confidence: 99%